Microcomputer application in production management / Roslan Abdul Ghani and Rahimi Muda - Abdul Ghani, Roslan; Muda, Rahimi (1986)
It is a scientific method which assesses alternative courses of action in a system provided an improved technique (ie computers) for management decision making, The attack of modern science on complex problems arising in the direction and management of large systems of men, machine material and money in industry business, government and defence. However in this section we will emphasized you the fields included in our analysis by using a computer programming under BASIC Languarge : (a) Work Study using Cumulative Time System. (b) Economic Order Quantity (EOQ). (c) Waiting Line Theory. (d) Linear Programming. (el Critical Path Analysis.